Do credit rating agencies add value? Evidence from the sovereign rating business institutions - Eduardo A. Cavallo; Andrew Powell; Roberto Rigobón (Inter-American Development Bank, Research Department, 2008)
If rating agencies add no new information to markets, their actions are not a public policy concern. But as rating changes may be anticipated, testing whether ratings add value is not straightforward. This paper argues that ratings and spreads are both noisy signals of fundamentals and suggest ratings add value if, controlling for spreads, they help explain other variables. The paper additionally analyzes the different actions (ratings and outlooks) of the three leading agencies for sovereign debt, also considering the differing effects of more or less anticipated events. The results are consistent across a wide range of tests. Ratings do matter and hence how the market for ratings functions may be a public policy concern.
Keywords: F37; G14; G15; C23; 330; Ratings; Spreads; Information Economics; Event Studies; Ratingagentur; Länderrisiko; Informationsökonomik; Zinsstruktur; Finanzmarkt